Does the scleral encircling band provide a protective effect against the progression of diabetic retinopathy? - Hossam Youssef Abouelkheir; Amani E Badawi; Amr M. Abdelkader; Amr El-Kanishy; Sameh Saleh; Waleed Ali Abou Samra; Manal Ali Kasem; Tharwat Mokbel (International Journal of Ophthalmology, 2019)
AIM: To evaluate the effect of scleral encircling bands on the development and progression of diabetic retinopathy (DR) in diabetic patients. METHODS: The medical records of diabetic patients who underwent unilateral retinal detachment (RD) surgery using scleral buckle and encircling band were reviewed retrospectively. Both eyes of patients were included in the study: one eye in each patient had a scleral buckle with encircling band (the operated eye) and the other one is the non-operated eye. The demographic characters, duration of diabetes and period between surgery and the last recall visit were retrieved from each patient. All the cases underwent fundus photo and fluorescein angiography (when indicated) to confirm the DR staging. RESULTS: Totally 25 patients fulfilled the inclusion and the exclusion criteria were become eligible for the study. A total of 50 eyes of 25 patients were enrolled in this analysis. The mean period of time passed from surgery with encircling band and the last reassessment visit was 12.5±2y. Even though DR could develop in the operated eyes, it was at a less degree of severity compared to the non-operated eyes of same patients (P=0.027). CONCLUSION: Scleral encircling bands have protective effects against the development and progression of DR.